Perancangan Keseimbangan Lintasan Produksi untuk Mengurangi Balance Delay dan Meningkatkan Efisiensi Kerja - Burhan -; Imron Rosyadi NR; Rakhmawati - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
The balancing of production lines is necessary to increase company’s efficiency and effectiveness to utilize the optimal production facilities. Insufficient balancing of production lines causes idle time in the form of bottleneck or delay. To ensure finishing product on time, company needs to consider live production lines. This work aimed to develop production line plan of PT. Madura Guano Industry In Bangkalan. Design of line balancing needs the processing data, processing times, and total output which resulted in a particular time. The data were analyzed using the Ranked Positional Weight and Region Approach method to determine effectiveness of work station, so that it could generate a minimum balance delay and rising work efficiency. Both methods produced the same results were decreasing balance delay (80% to 40%) and increasing work efficiency (20% to 60%) were noticed. The increasing of work efficiency resulted in an optimal production process.